Perancangan Interior Pusat Kecantikan dan Kebugaran di Kota Gorontalo - Lulu Holiangu (Intra, 2014)
Beauty and fitness center basically is a place for mind relaxation as well as for health care, especially for women. The density of activity in modern times has caused many women to be tired and bored. Therefore we need a facility that can accommodate all maintenance activities, not just the outer beauty treatments but also the beauty that comes from within the body. Beauty and fitness center is devoted to the women who need the opportunity for mind relaxation, also a facility to maintain health. By taking the concept of modern design but still refers to the cultural values of beauty and fitness center design is not only about beauty themselves but also help preserve the culture of Gorontalo area that is applied to the design of interior design